Recent Advances of Novel Pharmaceutical Designs for Anti-cancer Therapies - Biersack, Bernhard (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue covers a well-balanced collection of state-of-the-art topics in the prospering and competitive field of anticancer drug design and development, which can address and inspire oncologists, biologists, and medicinal chemists among the readership of this journal.